The effect of a combined high-intensity plyometric and speed training program on the running and jumping ability of male handball players - Cherif, M.; Said, M.; Chaatani, S.; Nejlaoui, O.; Gomri, D.; Abdallah, A. (Asian Journal of Sports Medicine, 2012)
Purpose: The aim of this study was to investigate the effect of a combined program including sprint repetitions and drop jump training in the same session on male handball players.